2004
DOI: 10.1902/jop.2004.75.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cigareté Smoking on Gingival Bleeding

Abstract: Smoking exerts a strong, chronic, and dose-dependent suppressive effect on gingival bleeding on probing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
164
7
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(202 citation statements)
references
References 35 publications
27
164
7
4
Order By: Relevance
“…In the present analyses, the assessment of gingivitis susceptibility was therefore restricted to sites without attachment loss. Furthermore, the analysis was restricted to never-smokers and ex-smokers who had quit at least 5 yrs previously, because of the strong suppressive effect of smoking on gingival bleeding (Bergström and Preber, 1986;Dietrich et al, 2004). Adjustment for smoking status (never vs. former) yielded identical results (data not shown).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present analyses, the assessment of gingivitis susceptibility was therefore restricted to sites without attachment loss. Furthermore, the analysis was restricted to never-smokers and ex-smokers who had quit at least 5 yrs previously, because of the strong suppressive effect of smoking on gingival bleeding (Bergström and Preber, 1986;Dietrich et al, 2004). Adjustment for smoking status (never vs. former) yielded identical results (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…Hence, once periodontitis is established, gingival bleeding due to gingivitis is impossible to distinguish from that due to periodontitis. Sites affected by periodontitis have showed more gingival bleeding, even if bleeding on probing was assessed at the marginal gingiva (Dietrich et al, 2004). In the present analyses, the assessment of gingivitis susceptibility was therefore restricted to sites without attachment loss.…”
Section: Discussionmentioning
confidence: 95%
“…11 Studies showed that the hemorrhagic responsiveness of the periodontium is suppressed by smoking. 12,13 There is a chronic reduction in blood flow and gingival crevicular fluid.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…High cigarette consumption amplifies clinical manifestations of chronic periodontal disease and demands increased treatment needs (Dietrich et al. 2004, Susin et al. 2004, Do et al.…”
mentioning
confidence: 99%